1982
DOI: 10.1128/jcm.16.3.422-426.1982
|View full text |Cite
|
Sign up to set email alerts
|

Prospective survey of fecal, urinary tract, and environmental colonization by Providencia stuartii in two geriatric wards

Abstract: A prospective survey offecal, urinary tract, and environmental colonization by Providencia stuartii in two wards was undertaken over a 5-month period. Eight of 53 male patients and 2 of 89 female patients were colonized with the endemic serotype 0:63. Two patterns of colonization were found on the male ward. Two patients had persistent urinary tract colonization with no detectable fecal carriage. The other patients had fecal carriage, in some cases persistent, with intermittent urinary tract colonization. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The predilection for Proteeae species to cause urinary tract infections in persons in chronic care facilities has been amply documented (2,7,9,13,14,16,20). Such infections are usually attributed to persistence of Proteeae species in catheterized subjects (20), along with opportunistic crossinfection among persons with urethral catheters (5,7,9). No reservoir has been previously identified in noncatheterized persons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The predilection for Proteeae species to cause urinary tract infections in persons in chronic care facilities has been amply documented (2,7,9,13,14,16,20). Such infections are usually attributed to persistence of Proteeae species in catheterized subjects (20), along with opportunistic crossinfection among persons with urethral catheters (5,7,9). No reservoir has been previously identified in noncatheterized persons.…”
Section: Discussionmentioning
confidence: 99%
“…In newly hospitalized patients, risk factors for a variety of asymptomatic and life-threatening aerobic gram-negative bacillus (AGNB) infections include both recent nursing home residence and prior indwelling urethral catheterization (7,14). In numerous studies among residents of chronic care facilities (7,9,13,16,18,20), Proteeae species (Morganella, Proteus, and Providencia) have been found to be prominent causes of urinary tract infections. On occasion, in a chronic treatment unit urinary tract infections due to Proteeae species have been disproportionately more frequent than infections due to Escherichia coli (13).…”
mentioning
confidence: 99%
“…and the white to grey colonies of the Eniterobacteriaceae; again, no data were provided on suitability for isolating Providencia spp. Primary isolation media incorporating the antibiotic colistin (or polymyxin B) have also been reported (4,8,14). Use of these media is permissible if a particular strain known to be colistin resistant is to be isolated.…”
Section: Discussionmentioning
confidence: 99%
“…The reservoirs and mode of spread of P.stuartii were poorly understood, as clusters of cases occurred with colonised urine in catheters as the presumed source of infection, at other times occurrence of overt infection was sporadic with no apparent source 2 . A detailed study of a male CoEW showed that faecal colonisation represented the most significant reservoir 3 . During the course of collecting strains for this study a series of isolates were obtained over a 20 month period from a patient with a long term urinary catheter colonised by a single serotype (O:63) of P.stuartii.…”
Section: Introductionmentioning
confidence: 99%